2021
DOI: 10.1177/07388942211012623
|View full text |Cite
|
Sign up to set email alerts
|

Extended intergroup contact in frozen conflicts: Experimental evidence from Cyprus

Abstract: How can ethnic reconciliation be achieved in conflict settings where populations are physically separated? We address this question by examining the role of “extended contact”—a form of indirect contact which entails learning about the contact experiences of others—in the context of Cyprus’s frozen conflict. We field a survey experiment in order to test two pathways through which extended contact works: (1) by helping build a common identity; and (2) by activating empathy. We find that our treatments are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…More recently, Psaltis and Cakal (2016) found that compared to those identifying as Greeks or Turks of Cyprus, participants identifying as Cypriot showed significantly lower levels of threat, prejudice, and distrust toward members of the opposing community. Donno et al (2021) findings also demonstrate that cueing common identity among religious Greek Cypriots can increase trust toward the Turkish Cypriot community. The present research builds on these findings by investigating how identifying with a superordinate category can shape Turkish Cypriot attitudes and behavioral tendencies toward the Greek Cypriot community.…”
Section: Ciimmentioning
confidence: 64%
“…More recently, Psaltis and Cakal (2016) found that compared to those identifying as Greeks or Turks of Cyprus, participants identifying as Cypriot showed significantly lower levels of threat, prejudice, and distrust toward members of the opposing community. Donno et al (2021) findings also demonstrate that cueing common identity among religious Greek Cypriots can increase trust toward the Turkish Cypriot community. The present research builds on these findings by investigating how identifying with a superordinate category can shape Turkish Cypriot attitudes and behavioral tendencies toward the Greek Cypriot community.…”
Section: Ciimmentioning
confidence: 64%
“…Studies have also shown that individuals respond differently to information about their in-group members based on the saliency of their in-group identity (e.g. Donno et al, 2021). In the case of XUAR, I expect the identity treatment to have a larger effect on individuals who report themselves to be religious and identify themselves as a Turk (as opposed to other ethnic groups in Turkey).…”
Section: Theory: Determinants Of Public Attitudesmentioning
confidence: 99%
“…Only within the last few decades have researchers begun to investigate how social and psychological processes associated with contact may function differently in contexts with legacies of prolonged—and often violent—conflict, as compared to less volatile settings (e.g., Donno et al, 2021; Tropp, 2015; Uluğ & Cohrs, 2017; Wagner & Hewstone, 2012). As such, much more remains to be uncovered regarding how contact may contribute to shaping relations between groups in contexts where group relations have been rooted in conflict.…”
Section: Intergroup Attitudes and Construals Of Intergroup Relations ...mentioning
confidence: 99%